The Translation Strategies in Translating Balinese Cultural Wordsinto English - Ria Saraswati (Universitas Bunda Mulia, 2017)
The aim of this research is to describe the strategies used by the translator in translating Balinese cultural words into English. The strategies in translation process should be defined as the consequence of translator’s effort to establish the exact meaning between two different language systems. A translator, in his attempt to transfer meaning from source language into target language, usually faces a set of problems; one of the problems is cultural words. It means to overcome the difficulties; the translator has proposed many possible strategies. The method used in this research is qualitative method. It means that all the data are words and sentences. In this research, descriptive can belong to qualitative research as there is a description of data from Indonesian and English book.And the sources of data used in this research is the Indonesian book Pantomime Suci Betara Berutuk Dari Trunyan, Bali (1985) by Prof. Dr. James Danandjaja and its English version Betara Berutuk Sacred Pantomime from Trunyan translated by the same person. The theory of translation strategies are the main theories used in this research. The theory is taken from Mona Baker, In other Words (1997). The use of translation strategies was analysed using her definitions.The data are classified into three main categories: translation using loan words, translation by cultural substitution, translation by paraphrasing and translation by general word. Translation using loan word is categorized into two sub-categories: transference and loan word plus explanation. Translation by paraphrasing is categorized into two sub-categories: paraphrasing using related word and paraphrasing using unrelated word. Keywords: Translation strategies, Balinese cultural words, loan word, paraphrasing, general wor